An improved miniprotein host for fluorogenic supramolecular assembly on the surface of living cells. Issue 24 (18th February 2016) - Xu, Bi; Zhou, Xinqi; Stains, Cliff I.
Abstract : A new host–guest pair produces a significant increase in the brightness of supramolecular complexes on the surface of living cells. Abstract : An improved miniprotein host capable of fluorogenic supramolecular assembly with a sI-Pht guest is reported. This improved host, termed 6.2.22, displays significant enhancements in both the EC50 for complexation and fluorescence activation of the sI-Pht guest, allowing for improved resolution of supramolecular complexation on the surface of living yeast.